2000
DOI: 10.1128/jvi.74.5.2247-2254.2000
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro- and In Vivo-Generated Defective RNAs of Satellite Panicum Mosaic Virus Define cis -Acting RNA Elements Required for Replication and Movement

Abstract: Satellite panicum mosaic virus (SPMV) depends on its helper virus, panicum mosaic virus (PMV),Four plant satellite viruses have been identified in association with helper viruses from natural infections, including satellite tobacco necrosis virus (STNV), satellite panicum mosaic virus (SPMV), satellite maize white line mosaic virus, and satellite tobacco mosaic virus (STMV) (4, 23). Satellite viruses are valuable tools for dissecting sequence or structural features of RNA molecules that are essential for biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The capsid protein also elicits symptoms on a nonhost plant, Nicotiana benthamiana (22), a feature that may be related to the unconventional role of SPMV CP in regulating a suppressor of gene silencing (22). SPMV CP is not essential for replication and systemic movement of the satellite virus RNA in millet plants (21). However, the absence of CP expression stimulated the accumulation of SPMV-defective interfering RNAs, suggesting an additional role of the CP in maintaining SPMV RNA integrity (24).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The capsid protein also elicits symptoms on a nonhost plant, Nicotiana benthamiana (22), a feature that may be related to the unconventional role of SPMV CP in regulating a suppressor of gene silencing (22). SPMV CP is not essential for replication and systemic movement of the satellite virus RNA in millet plants (21). However, the absence of CP expression stimulated the accumulation of SPMV-defective interfering RNAs, suggesting an additional role of the CP in maintaining SPMV RNA integrity (24).…”
mentioning
confidence: 99%
“…The CP is used to assemble 16-nm spherical satellite virus particles (19,21). As expected, SPMV CP has a high affinity for binding SPMV RNA, as shown by gel mobility shift assays (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They involve a small size virus (satellite virus) and a larger virus (helper virus). One of the most studied co-operations concerns the association of panicum mosaic satellite virus (PMSV) and panicum mosaic virus (PMV) (Qiu & Scholthof, 2000, 2001. It has been demonstrated that the smaller partner (satellite virus) needs the larger one for its replication, but that it is the satellite virus that induces severe chlorosis on proso millet plant (Qiu & Scholthof, 2001).…”
mentioning
confidence: 99%
“…These questions relate to host range determinants and reiterate the particular importance of host proteins. For example, studies with satellite panicum mosaic virus have shown that a small RNA element conveys a host-specific contribution to virus movement (Qiu and Scholthof, 2000), perhaps through its interaction with a host factor. Research with Tomato Bushy stunt virus on various plants showed that certain amino acids of a movement-associated protein need to be retained for activity in all its hosts but other residues have host-dependent activities (Chu et al, 2000).…”
Section: Virusesmentioning
confidence: 99%